1984
DOI: 10.1128/jvi.51.3.832-837.1984
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration in vitro that eucaryotic initiation factor 3 is active but that a cap-binding protein complex is inactive in poliovirus-infected HeLa cells

Abstract: Protein synthesis initiation factor preparations from poliovirus-infected HeLa cells have reduced ability to initiate translation on capped mRNA. The defect in initiation factors has been variously attributed to inactivation of eucaryotic initiation factor 3 (eIF3), eIF4B, or a cap-binding protein (CBP) complex. We have developed a series of in vitro protein synthesis assays to show that eIF3 is active but a CBP complex activity is inactivated after poliovirus infection. eIF3 activity, when determined in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(39 citation statements)
references
References 24 publications
(20 reference statements)
2
37
0
Order By: Relevance
“…In the case of entero‐, rhino‐, and aphthovirus genera, shut‐off of translation has been related to the functional inactivation of the eIF‐4F complex. Indeed, soon after infection of susceptible cells with these viruses, eIF‐4G (220 kDa) is cleaved giving rise to an amino‐terminal fragment of 13 kDa and to a carboxy fragment of 100 kDa [10, 7, 11, 12]. Both genetic and biochemical evidence supports the notion that virus‐encoded proteinases 2A pro (L pro in aphthovirus) are responsible for the proteolytic bissection of eIF‐4G [13–15].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In the case of entero‐, rhino‐, and aphthovirus genera, shut‐off of translation has been related to the functional inactivation of the eIF‐4F complex. Indeed, soon after infection of susceptible cells with these viruses, eIF‐4G (220 kDa) is cleaved giving rise to an amino‐terminal fragment of 13 kDa and to a carboxy fragment of 100 kDa [10, 7, 11, 12]. Both genetic and biochemical evidence supports the notion that virus‐encoded proteinases 2A pro (L pro in aphthovirus) are responsible for the proteolytic bissection of eIF‐4G [13–15].…”
Section: Introductionmentioning
confidence: 90%
“…Mammalian eIF‐4F has been purified as a complex of three polypeptides: eIF‐4E (24 kDa, cap‐binding protein), eIF‐4A (50 kDa, RNA helicase) and eIF‐4G (220 kDa) [4, 5]. The eIF‐4F complex interacts with other initiation factors, such as eIF‐3 and eIF‐4B to promote the entry of the small 40S ribosomal subunit to the mRNA [6–9].…”
Section: Introductionmentioning
confidence: 99%
“…In 1982 Etchison and Hershey made the seminal discovery that eIF4G (then called p220) was cleaved during PV infection, thus inactivating eIF4F complexes in cells (Etchison et al, 1982). Other reports demonstrated that eIF4E, eIF4A, eIF4B, eIF3 were not cleaved in PV-infected cells (Duncan et al, 1983;Etchison et al, 1984;Lee et al, 1985), however, PABP was independently reported by two groups to be cleaved by PV andCVB3 in 1999 (Joachims et al, 1999;Kerekatte et al, 1999). No other canonical translation factors are known to be cleaved during PV infection.…”
Section: Viral 2a Proteinases Cleave Eif4gi and Eif4giimentioning
confidence: 98%
“…The diminished ability of cell extracts from poliovirus-infected cells to translate capped mRNA species can be restored on the addition of eIF-4F preparations (Tahara et al, 1981;Grifo et al, 1983;Etchison et al, 1984;Edery et al, 19841, supporting the theory that it is the deficiency in this factor that is responsible, at least partially, for the virus-induced shut-off of the host protein synthesis. Importantly, no evidence for poliovirus infection-induced alterations of other constituents of eIF-4F, either eIF-4A or eIF-4E, nor of another participant of the RNA-ribosome interaction, eIF-4B, was found (Helentjaris et al, 1979;Duncan et al, 1983;Etchison et al, 1984;Lee et al, 1985;Buckley and Ehrenfeld, 1986). Since poliovirus mutants unable to induce efficient inactivation of eIF-4F, being viable, grow relatively poorly (Bernstein et al, 1985), it seems likely that the inhibition of the capdependent initiation machinery is beneficial for the virus because it eliminates competition with other templates.…”
Section: B Initiation Factor Requirements For the Translation Of Picmentioning
confidence: 95%
“…Moreover, the p220 subunit of eIF-4F is degraded on enterovirus (Etchison et al, 1982;Lee et al, 1985;Buckley and Ehrenfeld, 1987), rhinovirus (Etchison and Fout, 19851, and aphthovirus (Lloyd et al, 1988;Devaney et al, 1988) [but not cardiovirus (Mosenkis et al, 1985;Lloyd et al, 1988)l infections, rendering the host cell protein-synthesizing machinery unable to efficiently initiate translation of capped mRNAs, while retaining, if not increasing, the capacity to utilize uncapped picornaviral templates (Kaufmann et al, 1976;Helentjaris and Ehrenfeld, 1978;Rose et al, 1978;reviewed by Ehrenfeld, 1984;Kozak, 1986d;Sonenberg, 1987). The diminished ability of cell extracts from poliovirus-infected cells to translate capped mRNA species can be restored on the addition of eIF-4F preparations (Tahara et al, 1981;Grifo et al, 1983;Etchison et al, 1984;Edery et al, 19841, supporting the theory that it is the deficiency in this factor that is responsible, at least partially, for the virus-induced shut-off of the host protein synthesis. Importantly, no evidence for poliovirus infection-induced alterations of other constituents of eIF-4F, either eIF-4A or eIF-4E, nor of another participant of the RNA-ribosome interaction, eIF-4B, was found (Helentjaris et al, 1979;Duncan et al, 1983;Etchison et al, 1984;Lee et al, 1985;Buckley and Ehrenfeld, 1986).…”
Section: B Initiation Factor Requirements For the Translation Of Picmentioning
confidence: 99%